Homiletika Pasca-Manusia: Ketika Firman Dikumandangkan Oleh Mesin Dan Didengar Oleh Jiwa Yang Lelah - Alelang Deprolius Bang; Maruhal Siringoringo (Sekolah Tinggi Teologi Sriwijaya, 2026)
This study examines the dynamics of homiletics in the posthuman era, where the proclamation of God's Word is increasingly mediated by artificial intelligence and received by individuals experiencing existential exhaustion. The research asks how artificial intelligence reshapes the nature of homiletics and to what extent the spiritual dimension of preaching can be sustained within digital environments. Accordingly, the study aims to analyze the relationship between artificial intelligence, digital media, and the proclamation of the Word from the perspective of practical theology. Employing a qualitative-descriptive approach, the research utilizes theological hermeneutics and an interdisciplinary literature review encompassing theology, philosophy of technology, and digital communication. The findings reveal that although artificial intelligence can replicate the rhetorical form and structural composition of sermons, it remains incapable of embodying the transcendent spiritual dimension without the participation of human consciousness, lived faith, and spiritual experience. The interaction between algorithmic systems and the human soul opens new horizons for theological reflection concerning divine presence in digital spaces. The study concludes that posthuman homiletics requires a reconstruction of the relationship between the Word, its communicative medium, and its hearers, while affirming that God's presence transcends technological limitations and can nevertheless be proclaimed creatively through digitally mediated platforms that retain genuine spiritual significance.